Adult-Onset Still’s Disease: Delayed Diagnosis Persists - Wahinuddin Sulaiman; Farisya Mohd Lepatoni (Asian Journal of Medicine & Health Sciences, 2023)
Adult-onset Still’s disease (AOSD) is a rare inflammatory condition of unknown etiology, that is characterised by quotidian high spiking fever, polyarthritis, evanescent rash, and hyperferritinemia. AOSD is a diagnosis by exclusion, and it is one of the common causes of pyrexia of unknown origin (PUO) which can be life threatening if mistreated. Treatment may pose a great challenge. We report a young woman who presented with PUO, rashes, progressive and debilitating polyarthritis for 10 months duration. Serological markers were negative except for ANA (speckled pattern, 1:160). Serum ferritin, C-reactive protein (CRP), and erythrocyte sedimentation rate (ESR) were markedly raised. She achieved remission after about 6 months of treatment with a combination of multiple immunosuppressants and corticosteroids.